Spatial contrast of the slums in the unity of the new municipal of Baghdad (Journal of the College of Education for Women, 2019)
The slums one of the main problem plaguing the city of Baghdad in general andthe unity of municipality of New Baghdad, especially, where the characteristics of the studyarea a prominent role in population growth and the emergence of slums where a private,although the region suffer from the housing crisis is the lack of the number of housing unitscompared to the number of families in which, With high land prices and the level of rentwhich was accompanied by the absence of the law, which was followed by the year 2003, hasbecome the study area and one of the most municipalities of the city of Baghdad Containslums which took fills abandoned buildings and acquires vacant land agricultural ones andallocated to different uses and which has not been implemented design basis so far, andshowed the study about the clarity of the features of this problem and the importance ofstudying it is not just slums scattered here and there, but it is clearly visible, and a largesurface area and the number of families and the number of residential subdivision, whichthreatens the problems and the effects of her land uses and private uses of the land residential